The impact of double tax treaties on inward FDI in ASEAN countries - DONG, Yue (Institutional Knowledge at Singapore Management University, 2019)
This study aims to assess the impact of double taxation treaties (DTT) on FDI inflows in 10 ASEAN countries from 1989 to 2016. There are two objectives of double taxation treaties. The first one is to alleviate the problem of global double taxation, which has a stimulating effect on FDI. The second objective is the sharing of information between governments, which can prevent tax evasion and thus discourage FDI. The findings suggest that new DTTs in ASEAN have a positive but insignificant impact on the FDI inflows into the region. However, the impact of old DTTs on FDI is significantly negative, suggesting that as the age of ASEAN countries’ DTTs could adversely affect FDI inflows. The possible explanation is that most of the ASEAN member countries are developing countries, which have experienced fiscal and regulatory reforms over the past few decades. Those policy reforms may have overtaken the terms of the prevailing bilateral tax treaty, meaning that some of the treaties, if not ratified, could have become obsolete. In addition, the recent trend in bilateral tax treaty negotiations globally has been towards lower withholding tax rates for investment income. Older treaties, which impose relatively high withholding tax rates, may become an impediment to the region’s cross-border investment and hinder economic growth. An examination of the DTTs signed by ASEAN countries further demonstrates that the member states vary considerably in the design of their treaties, in the way they divide up the tax base between source and resident countries, and also in the level of efforts to keep pace with the latest development in the OECD and UN Model Tax Conventions.